2019
DOI: 10.1105/tpc.18.00613
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale Sequence Disruption Following Biolistic Transformation in Rice and Maize

Abstract: Biolistic transformation delivers nucleic acids into plant cells by bombarding the cells with microprojectiles, which are micron-scale, typically gold particles. Despite the wide use of this technique, little is known about its effect on the cell's genome. We biolistically transformed linear 48-kb phage lambda and two different circular plasmids into rice (Oryza sativa) and maize (Zea mays) and analyzed the results by whole genome sequencing and optical mapping. Although some transgenic events showed simple in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 83 publications
0
69
1
Order By: Relevance
“…It is known that biolistic-mediated DNA delivery can lead to insertion of plasmid DNA, often fragmented, into random genome locations in plants 34,35 . However, this unintended DNA insertion is underreported in the literature and when reported, the detailed data were often not supplied in the publications.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that biolistic-mediated DNA delivery can lead to insertion of plasmid DNA, often fragmented, into random genome locations in plants 34,35 . However, this unintended DNA insertion is underreported in the literature and when reported, the detailed data were often not supplied in the publications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we believe that the effects observed were due to the construct inserting in a gene and interfering with its normal function. A recent study on the effects of biolistic transformation on the broader genome found numerous examples of chromosomal damage, deletions, broken transgenes, and other unintended effects [19]. Table shows the number of plants in each group).…”
Section: Alterations In Protein and Seed Size Resulting From A Transgmentioning
confidence: 99%
“…Tree diagram shows the phylogenetic relationship between Agrobacterium and other non-Agrobacterium species belong to the common order Rhizobiales (Slater et al, 2009). many crops like tobacco,soybean, rice, maize (Liu et al, 2019), wheat (Lazzeri, 1999), cotton (Raj asekaran, 2013),mango (Andres Cruz-Hernandez)etc., the DNA coating over the carrier is very important and many protocols have been developed while the generally used methods were Ca2+ protocol and PEG /MgCl2 protocol. the DNA and adhesive chemical mixture in micro-vial are constantly vortexed to prepare microcarrier (Rajasekaran, 2013).…”
Section: Figmentioning
confidence: 99%
“…The gene gun is fixed inside the aseptic condition generally laminar air flow chamber to facilitate transformation without contamination. The material to be transferred is bombarded to a maximum of one time because more times of bombardment will causetissue damage, chromosome truncations, large deletions, partial trisomy and breakage-fusion bridge cycling, etc., (Liu et al, 2019) which ultimately may cause mortality. The plants that show low response to tissue culture find difficult to use gene gun for the transformation of a gene.…”
Section: Figmentioning
confidence: 99%